PENGARUH PENGGUNAAN MODEL PEMBELAJARAN ROTATING TRIO EXCHANGE TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AL-ISLAM KELAS X DI SMA MUHAMMADIYAH 1 PALEMBANG - Habibur Rachman; Zuhdiyah Zuhdiyah; Yuniar Yuniar; Rulitawati Rulitawati (Raudhah - Proud To Be Professional, 2024)
Abstract: This research aims to analyze the influence of the Rotating Trio Exchange learning model on student’s learning motivation in class X Al-Islam subjects at SMA Muhammadiyah 1 Palembang. The Rotating Trio Exchange learning model explains that rotating three-person exchanges of opinions are a detailed way for students to discuss promblem with their classmates. This research was motivated by the decreasing motivation of class X student’s learning outcomes at SMA Muhammadiyah 1 Palembang. The method used is a quantitative method, namely examining a sample that has been determined to be 72 respondents as students by collecting data using questionnaires and learning outcomes test, analyzed using statistics. The results of the reearch show that there is a significant influence of using the Rotating Trio Exchange. Keywords: Parenting patterns, Motivation, Religious Character